Promoting Speaking Skills of the School Students Using Technology - Pushpalatha, U. (International Journal of Psychosocial Rehabilitation, 2020)
Speaking is an important skill to survive in this world. The major aim of learning new language is communication. To speak any language, one must listen first. Speaking and listening are interrelated. Both the skills integrate help each other to grow parallel. Listening must be trained properly and regularly to improve speaking skill. Listening is passive but speaking is an active skill. This paper focuses on improving speaking skills of the school students, particularly L1 background students. To develop speaking skill, practice-oriented sessions conducted. There was no paper and pen work, no drilling and rote-learning. This study trained with free hands but mind and mouth engaged. It focuses school students because it is very easy to shape them and also it is needed for them to go for higher studies. Regular practice is important to enrich this skill. Speaking skill brings confidence to learn English better.Technology is the boon for the present generation students. Students’ of this generation are very much like to learn through mobile and internet. Technology integrated learning is an effective learning process. It is very useful for the students to learn easily as well as effectively. Opportunities are vast nowadays for learning through technology. It should be properly utilized to promote the skills of the students.